2022
DOI: 10.1186/s40104-022-00793-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate alleviates deoxynivalenol-induced hepatic cholesterol metabolic dysfunction via RORγ-mediated histone acetylation modification in weaning piglets

Abstract: Background Cholesterol is an essential component of lipid rafts in cell plasma membrane, which exerts a hepatoprotective role against mycotoxin exposure in pigs, and cholesterol metabolism is vulnerable to epigenetic histone acetylation. Therefore, our present study aimed to investigate whether a histone deacetylase inhibitor (sodium butyrate [NaBu]) could protect the porcine liver from deoxynivalenol (DON) exposure by modulating cholesterol metabolism. Herein, we randomly divided 28 pigs into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Biochemical indexes are important parameters for assessing the welfare of aquatic animals ( Mitranescu et al., 2013 ), and adjusting these indexes can better meet the living conditions of aquatic animals and promote their growth and development. In our study, TC levels in the blood of Chinese soft-shelled turtles fed with SB were lower than those of turtles fed without it, and this was closely related to the increase in SB concentration ( Zong et al., 2022 ). Studies have shown that adding 1–2 mg of SB to the diet of Nile tilapia juveniles can significantly improve the activities of TP and transaminase ( Abdel-Latif et al., 2021 ).…”
Section: Discussionmentioning
confidence: 50%
“…Biochemical indexes are important parameters for assessing the welfare of aquatic animals ( Mitranescu et al., 2013 ), and adjusting these indexes can better meet the living conditions of aquatic animals and promote their growth and development. In our study, TC levels in the blood of Chinese soft-shelled turtles fed with SB were lower than those of turtles fed without it, and this was closely related to the increase in SB concentration ( Zong et al., 2022 ). Studies have shown that adding 1–2 mg of SB to the diet of Nile tilapia juveniles can significantly improve the activities of TP and transaminase ( Abdel-Latif et al., 2021 ).…”
Section: Discussionmentioning
confidence: 50%
“…Consistent with this result, it has been documented that a complex mycotoxin supplementation in pig feed could markedly reduce H3K27ac genome-wide binding in the pig liver. 58 Notably, the cofactors we focused on in the present study expound the contradicted gene expression profiles in DON/LCA treatments and will benefit further exploration in mycotoxin-induced discrepant transcriptional programming.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, COS 2 and COS 3 were found to promote the growth of intestinal probiotics such as Bifidobacterium and Lactobacillus in ob/ob model mice and significantly increase the abundance of functional microbial communities, such as Akkermansia , Clostridiales , Faecalibaculum , Roseburia , Ruminiclostridium , and Alistipes , which are also known to produce butyric acid. Previous study reported that butyrate had been reported to induce the reduction of lipid accumulation (Zong et al 2023 ). For the intervention mechanism investigation, NaB-induced PPARα activation stimulates fatty acid β oxidation, thus contributing to amelioration of high-fat diet-induced NAFLD in adult rats (Sun et al 2018 ).…”
Section: Discussionmentioning
confidence: 97%